2014
DOI: 10.1111/1556-4029.12377
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Method to Correlate Bloodstains with Wound Site for Crime Scene Reconstruction

Abstract: Bloodstain pattern analysis to determine the wound-of-origin of bloodstains is problematic with nonspecific patterns. In this proof-of-concept study, the authors examined a molecular approach to correlate bloodstains with injuries using the rat as a model. Specifically, investigations were conducted on the rat brain marker, rno-miR-124-3p, with the QIAGEN miScript System and real-time PCR analysis. Rno-miR-124-3p was detected in brain homogenates diluted 100,000 times; in 3-week-old, room temperature stored, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Quantitative real-time PCR (qRT-PCR) was performed with a miScript System (Qiagen, USA), as previously described (Wang et al 2010), which included specific primers for miR-21 (5′-UAGCUUAUCAGACUGAUGUUGA-3′). Gene expression was evaluated by iCycler iQ real-time PCR detection system (BioRad Laboratories, Milano, MI, Italy), using the SYBRGreen as fluorochrome, as previously described (Johnson et al 2014). Reactions were performed under the following conditions: 95°C 15 min; 94°C 15 s, 55°C 30 s, 70°C 30 s, 40 cycles.…”
Section: Mir-21 Analysismentioning
confidence: 99%
“…Quantitative real-time PCR (qRT-PCR) was performed with a miScript System (Qiagen, USA), as previously described (Wang et al 2010), which included specific primers for miR-21 (5′-UAGCUUAUCAGACUGAUGUUGA-3′). Gene expression was evaluated by iCycler iQ real-time PCR detection system (BioRad Laboratories, Milano, MI, Italy), using the SYBRGreen as fluorochrome, as previously described (Johnson et al 2014). Reactions were performed under the following conditions: 95°C 15 min; 94°C 15 s, 55°C 30 s, 70°C 30 s, 40 cycles.…”
Section: Mir-21 Analysismentioning
confidence: 99%
“…However, the results of this study indicate that wound cells may vary in amounts from pattern to pattern, and from bloodstain to bloodstain within a pattern. A nonuniform distribution of wound cells was also observed by the authors with gunshot blood spatter patterns (7). Sampling strategies in casework will have to consider the possibility of a heterogeneous distribution of wound cells across bloodstains of a pattern.…”
Section: Discussionmentioning
confidence: 72%
“…In a previous study, the authors demonstrated that blood spatter resultant of a gunshot wound can contain trace quantities of wound cells . Moreover, the study showed that wound cells can provide information on the anatomical site of origin of the bloodstains.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations